EXPERIENCE OF CONSTRUCTION OF PRODUCTION FUNCTION FOR DONBAS MINES - LEVCHENKO, O.; PIDTILOK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Central and Western Donbas shaft examples were used to design the operating functions based on the parameters which reflect exact expenditures and work-over resources availability. Causal-investigatory relationships between efficiency of resources charge and mining conditions have been analyzed.